An Eph receptor sperm-sensing control mechanism for oocyte meiotic maturation in Caenorhabditis elegans - Miller, Michael A. (Cold Spring Harbor Laboratory Press, 2003)
During sexual reproduction in most animals, oocytes arrest in meiotic prophase and resume meiosis (meiotic maturation) in response to sperm or somatic cell signals. Despite progress in delineating mitogen-activated protein kinase (MAPK) and CDK/cyclin activation pathways involved in meiotic maturation, it is less clear how these pathways are regulated at the cell surface. The Caenorhabditis elegans major sperm protein (MSP) signals oocytes, which are arrested in meiotic prophase, to resume meiosis and ovulate. We used DNA microarray data and an in situ binding assay to identify the VAB-1 Eph receptor protein–tyrosine kinase as an MSP receptor. We show that VAB-1 and a somatic gonadal sheath cell-dependent pathway, defined by the CEH-18 POU-class homeoprotein, negatively regulate meiotic maturation and MAPK activation. MSP antagonizes these inhibitory signaling circuits, in part by binding VAB-1 on oocytes and sheath cells. Our results define a sperm-sensing control mechanism that inhibits oocyte maturation, MAPK activation, and ovulation when sperm are unavailable for fertilization. MSP-domain proteins are found in diverse animal taxa, where they may regulate contact-dependent Eph receptor signaling pathways.